Design and Characterization of Maltoheptaose-b-Polystyrene Nanoparticles, as a Potential New Nanocarrier for Oral Delivery of Tamoxifen - Marcos Antonio Villetti (MDPI AG, 2021)
Tamoxifen citrate (TMC), a non-steroidal antiestrogen drug used for the treatment of breast cancer, was loaded in a block copolymer of maltoheptaose-b-polystyrene (MH-b-PS) nanoparticles, a potential drug delivery system to optimize oral chemotherapy. The nanoparticles were obtained from self-assembly of MH-b-PS using the standard and reverse nanoprecipitation methods. The MH-b-PS@TMC nanoparticles were characterized by their physicochemical properties, morphology, drug loading and encapsulation efficiency, and release kinetic profile in simulated intestinal fluid (pH 7.4). Finally, their cytotoxicity towards the human breast carcinoma MCF-7 cell line was assessed. The standard nanoprecipitation method proved to be more efficient than reverse nanoprecipitation to produce nanoparticles with small size and narrow particle size distribution. Moreover, tamoxifen-loaded nanoparticles displayed spherical morphology, a positive zeta potential and high drug content (238.6 ± 6.8 µg mL−1) and encapsulation efficiency (80.9 ± 0.4 %). In vitro drug release kinetics showed a burst release at early time points, followed by a sustained release profile controlled by diffusion. MH-b-PS@TMC nanoparticles showed higher cytotoxicity towards MCF-7 cells than free tamoxifen citrate, confirming their effectiveness as a delivery system for administration of lipophilic anticancer drugs.